The dating of the ornithological section of Middendorff's Reise in den äussersten Norden und Osten Sibiriens, with comments on the nomenclature of Pallas’s Bunting Emberiza pallasi Cabanis (Aves: Emberizidae) - Mlíkovský, Jiří (Zootaxa, 2014)
Middendorff's work on the Säugethiere, Vögel und Amphibien, published as part 2 of volume 2 of his Reise in den äussersten Norden und Osten Sibiriens, was variably dated from 1851, 1852 or 1853. I document that the work was published shortly before 15 December 1852 and I recommend using this date for the purposes of zoological nomenclature.Due to this, Emberiza polaris Middendorff, 1852 has precedence over Cynchramus pallasi Cabanis, 1853. This bunting species thus should be called Emberiza polaris and its four subspecies should be called Emberiza polaris polaris Middendorff, 1852, E. polaris minor Middendorff, 1852, E. polaris pallasi (Cabanis, 1853) and E. polaris lydiae Portenko, 1929.